GLOBAL DEVELOPMENT FINANCE 2002 Vol 1 : Financing the Poorest Countries. ANALYSIS AND SUMMARY TABLES - World Bank (Global Development Finance, 2002)
There is a more recent edition of this title available! This is an annual publication; the new edition is available for ordering or pre-ordering. Global Development Finance 2003 Vol 1 & 2 (Complete Print Edition)